First principles studies of MCO3 (M: Ca, Mn, Fe,Co, Ni) precursor materials for Li-ion battries - Morukuladi, Mogahabo Tebogo (My University, 2020)
The need for improved, reliable and efficient energy storage devices such as lithium-ion rechargeable batteries have increased, in particular the cathode materials for Li-ion batteries. The currently used cathode material lithium cobalt oxide (LCO) have been reported to be toxic, expensive and scarcity of cobalt. However, Nickel Manganese Cobalt (NMC) have been reported as alternate cathode materials for lithium ion batteries due to their availability, affordability and non-toxic nature. Moreover, Lithium and manganese-rich composites Li1+xM1-xO2 have gained lots of attention as future cathode materials for Li-ion batteries due to their high capacity (>250mAh/g) and improved structural stability. The electrochemical performances of these compounds depends mainly on the physical properties of the precursor material which are synthesised via calcination. Precursor materials serve as source of lithium in lithium and manganese rich composites. Generally, precursor materials are a mixture of two or more substances that occur in a chemical reaction yielding other substances at the completion of a chemical reaction. In this work we initially perform preliminary first-principles density functional theory (DFT) studies to investigate the structural, thermodynamic, electronic and mechanical properties for transition metal carbonate precursor materials using the Vienna ab-initio simulation package (VASP) code. In particular, we calculate the cell parameters, heats of formation, density of states, band structures, elastic constants and phonon dispersion curves to mimic stability trend for MCO3. Moreover, cluster expansion methods were employed to determine the phase stability of Ni1-xMnxCO3, Co1-xNixCO3, and Co1-xMnxCO3 structures using the Universal Cluster Expansion (UNCLE) code. The structural lattice parameters were calculated to 95% agreement with the experimental data, ensuring robustness of the approach employed. The thermodynamic heats of formation were predicted to increase with the atomic mass of the transition metal except for CoCO3 and NiCO3, suggesting that CaCO3 is the most stable carbonate while CoCO3 is least stable. From the calculated elastic properties, we noted that transition metal carbonates in CaCO3, MnCO3, CoCO3 and NiCO3 satisfied the necessary stability criterion for trigonal crystal system, suggesting mechanical stability. On the other hand, FeCO3 was predicted to be unstable since the stability criterion (𝐶44+𝐶12)𝐶33−2𝐶132>0 and (𝐶11+𝐶12)𝐶44−2𝐶142>0 were not satisfied. The calculated phonon dispersion curves showed positive vibrations in the Brillouin zone indicating vibrational stability for CaCO3, MnCO3, NiCO3 and CoCO3 while on the other hand FeCO3 displayed the negative vibrations along the high Brillouin zone suggesting vibrational instability. The analysis of electronic structures showed that CaCO3 and MnCO3 are insulators due to the presence of relatively wide band gaps. On the other hand, CoCO3 and NiCO3 are semiconductors while FeCO3 showed metallic behaviour. Furthermore, the binary phase diagram from cluster expansion calculations generated new mixed Ni1-xMnxCO3 phases with the most stable phase favouring the Mn-rich side while Co1-xNixCO3 and Co1-xMnxCO3 are favourable at equiatomic (50:50) concentration.
Thesis (M.Sc. (Physics)) -- University of Limpopo, 2020
Keywords: Transition metal; Calcination; Batteries; Transition metal carbonates; Lithium ion batteries; Precursor materials; Cobalt compounds; Lithium compounds; Lithium ion batteries; Chemistry, Inorganic; Cathodes